Morphology, ultramorpholgy and morphometry of the fat body of virgin females and queens of the ants Pachycondyla striata (Hymenoptera : Formicidae) - Thiele, E. [UNESP]; Camargo-Mathias, M. I. [UNESP] (California State University, 2003)
The fat body cells of virgin females and queens of Pachycondyla striata ants belonging to the subfamily Ponerinae are illustrated from morphologic, ultramorphologic and morphometric viewpoints. Camera lucida drawing techniques were used, as well as scanning electronic microscopy (SEM). Measurements of trophocytes and oenocytes areas in the tissue were recorded. The results showed that in P. striata queens and virgin females the trophocytes are arranged in cord-like formations in association with oenocytes. Trophocytes of both castes had round shapes, with rather vacuolized cytoplasm, whereas oenocytes, being smaller than trophocytes, had more homogeneous cytoplasm. It was also observed that both trophocytes and oenocytes of virgin females were larger than those found in the same queen cellular types.
Keywords: Pachycondyla striata; fat body; morphology; morphometry; scanning electron microscopy (SEM); ants